Assessment of the quality of life and self-esteem of mastectomized patients submitted or not to breast reconstruction - Vanessa Lacerda Alves; Miguel Sabino Neto; Luiz Eduardo Felipe Abla; Carlos Jorge Rocha de Oliveira; Lydia Masako Ferreira (Revista Brasileira de Cirurgia Plástica)
INTRODUCTION: After diagnosis and treatment of breast cancer, some women go through physical, social, and emotional changes that often have an impact on their quality of life and self-esteem. This study aimed to assess the quality of life and self-esteem of mastectomized patients with or without breast reconstruction a month after surgery. METHODS: The study consisted of 89 patients aged ≥ 30 years with or without breast reconstruction. They were recruited from the Plastic Surgery and Mastology clinic of São Paulo Hospital and Pérola Byington Hospital. Group 1 (n = 30) consisted of mastectomized patients without breast reconstruction; group 2 (n = 29) consisted of mastectomized patients with breast reconstruction; and group 3 (n = 30) consisted of patients without changes in the breasts. The EORTC QLQ-C30 and Rosenberg Self-Esteem Scale UNIFESP/EPM instruments, which are validated in Brazil, were used to assess their quality of life. RESULTS: There were no observed effects in the quality of life and self-esteem of the patients who underwent mastectomy with or without breast reconstruction a month after surgery. CONCLUSION: The women with mastectomy with or without breast reconstruction a month after surgery showed no changes in their quality of life and self-esteem when compared among themselves and to women with no cancer history. It is necessary that this assessment, employing the EORTC QLQ-C30 and QLQ-BR23 questionnaires, be performed from the time of breast cancer diagnosis until after breast reconstruction to identify the stage when the quality of life and self-esteem are affected.